PENERAPAN PENDEKATAN PEMBELAJARAN MSHR UNTUK MENINGKATKAN SIKAP ILMIAH SISWA DI KELAS VIII SMP NEGERI 8 PEKANBARU - Neli Safitri (STKIP Pesisir Selatan, 2019)
The aim of this research is to improve learning outcomes in the attitudes domain, especially scientific attitudes as the main foundation for the formation of quality human resources. The approach used in this learning is motivation, socialization, habituation and remediation (MSHR) developed by the Physics Education Study Program FKIP Pekanbaru Riau University. The research method used is classroom action research consisting of three cycles in science subjects. The subjects of this study were class VIII-5 of SMP Negeri 8 Pekanbaru in the 2017-2018 school year consisting of 42 students. The results of this study indicate that the learning approach used can be declared effective to improve the competency of students' scientific attitudes, with a high category